The Impact of Work Discipline, OCB, and Compensation on the Performance of Community-Based Tourism Managers in Ketapanrame - 'Alallah, Mutawakkil; Fahimah, Mar'atul (JENIUS (Jurnal Ilmiah Manajemen Sumber Daya Manusia), 2026)
This study aims to analyze the influence of Work Discipline, Organizational Citizenship Behavior (OCB), and Compensation on the performance of Community Based Tourism Organization (CBTO) in Ketapanrame Tourism Village. In contrast to previous literature that generally places discipline and material compensation as the main predictors of performance in corporate structures, this study explores the unique dynamics of community-based tourism organizations. Using a quantitative method with an associative causal design and a saturated sampling technique (census) of 49 respondents, the data was analyzed using multiple linear regression assisted by the SPSS version 27 program. The results of the simultaneous regression test showed that the three variables contributed significantly by 40.3% to the variation in organizational performance (R² = 0.403; F count = 10.113; sig = 0.000). However, the partial test presents findings that contradict conventional management theory. Work Discipline (Regression Coefficient = 0.342; t count = 1.232; sig = 0.224) and Compensation (Regression Coefficient = 0.066; t count = 0.229; sig = 0.820) were shown to have no significant effect on performance. On the other hand, OCB was shown to have a positive and significant effect, and appeared as the most dominant predictor (Regression Coefficient = 1.017; t count = 3.951; sig = 0.000). These findings confirm that CBTO members' performance is not driven by rigid regulations or transactional (financial) motivation, but rather relies heavily on extra-role behavior, altruism, and a culture of mutual cooperation that goes beyond formal job descriptions.